Aplikasi Absensi Berbasis Pangenalan wajah Multiple Person - Rompas, Alexander Christian; Sompie, Sherwin; Jacobus, Agustinus (Universitas Sam Ratulangi, 2021)
Abstract - The attendance system is a feature used to record the attendance of certain activities such as academic activities. The manual attendance system has drawbacks in the form of discrepancies in the absences recapitulation, loss of attendance data, and the existence of absent data manipulation. The research with the title